Integrating Reduplication Patterns in The Western Flores Languages - Salahuddin Salahuddin (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This study aims to look at the reduplication patterns in the Western Languages of Flores, i.e., MRK Language Subgroup (Manggarai, Rembong, and Komodo). These three languages are grouped according to the results of the calculation of the percentage of similar languages made by Fernandez (1996). Data was collected through secondary data collection from pre-existing datasets, including field notes and dictionaries. Direct interviews with native speakers representing each language strengthen secondary data with more in-depth information. The analysis revealed that there are similar patterns found in full reduplication accompanied by changes in vowel phonemes as in laki-lako 'going everywhere' in Manggarai, zupak-zapaq 'hassle' in Rembong, and cuki-cake 'naughty' in Komodo. Partial reduplication, on the other hand, generally takes the form of adding or removing final phonemes in repeated words, for example, bingi-bangas 'dull-witted' in the Manggarai Language, daki-dekang 'helping each other' in the Rembong Language, and hipi-hapek 'going here and there' in Komodo Language. The Rembong Language has a distinctive partial reduplication, the presence of rhyme sounds at the beginning as in ghali-ghewe 'miserable life' and at the end of words as in kameq-mok 'sucks'. Partial reduplication in Komodo Language only involves the repetition of the initial syllable as in kekaro (karo-karo) 'walkings'. It is hoped that this research can be a reference for further research to explore more deeply reduplication in the MRK Language, either refuting the results in this research or supporting it by providing more data